Hegemoni Media Sosial terhadap Pendidikan Akhlak Siswa Sekolah Dasar - Fadhilah (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
The rapid development of digital technology has positioned social media as a dominant space influencing the moral construction of elementary school students. This study aims to analyze the forms and mechanisms of social media hegemony and its implications for moral education (pendidikan akhlak) in elementary school students. Employing a qualitative descriptive approach with a case study design, this research involved Islamic Education teachers, classroom teachers, and upper-grade students (IV–VI) as participants selected through purposive sampling. Data were collected via in-depth interviews, observations, and documentary studies, and analyzed using the Miles and Huberman interactive model. The findings indicate that social media functions as a hegemonic force through the dominance of daily activities, with 55% of students accessing social media for 1–3 hours per day. This phenomenon triggers behavioral changes, such as the imitation of impolite language and the lifestyles of digital influencers, leading to the weakening of moral value internalization within the school environment. Although anomalous data suggest that parental guidance can serve as a counter-hegemonic instrument, social media has generally created a new "common sense" that challenges normative values. The study concludes that moral education in the digital age requires an integrative strategy combining value cultivation, critical digital literacy, and synergistic collaboration between schools and families.